WEB-BASED ACCEPTANCE INFORMATION SYSTEM DESIGN IN SMP 2 SIANTAR - Sanjaya Pinem; Febrianto Sibuea (Sean Institute, 2019)
Admission of new students is one of the processes that exist in educational institutions such as schools that are useful for screening prospective students who are selected according to the criteria determined by the school to become their students. In general, the admission process for new students is carried out through the stages of registration, input grades, and announcements of student admissions. In this study, the application was carried out at SMP Negeri 2 Siantar which had been done manually or computerized but used Microsoft Office Excel, which allowed there to be a lot of data shortages. The problem formulation of this research is how to create an information system for new student admissions at SMP Negeri 2 Siantar. The research method used is literature, observation, analysis, design, testing and implementation. This new admissions information system is built using the PHP programming language and utilizes the MySQL database as a database server. The results of this study are a web-based admissions information system that has the ability to provide convenience for parents of prospective new students to obtain all information about new student admissions and carry out the online registration process.